Russian Federation - Per Capita Financing of Education : Experience and Issues - World Bank (World Bank Country Office, Moscow, 2013)
This brief policy note reviews experience so far with the implementation of a new financing scheme for general education (based on the principle of 'money follows the student') in the Russian Federation. The policy note, which also briefly discusses the lessons of international experience in the field, may be relevant to other countries that are in the process of moving to a system of per capita financing of education services. Of the four major issues facing the education sector in Russia - resource mobilization and efficiency, quality and output measurement, market linkages and equity and access - the first is central: other reforms will be difficult to implement without an improvement in mobilization and allocation of resources. Two key sets of issues are discussed: 1) those issues that have affected the smooth introduction of per capita financing to date in Russia; and 2) perceived problems in relation to budget flexibility and school autonomy because of the introduction of the Treasury system and the Budget Code.